Reexamining the Association of Body Mass Index With Overall Survival Outcomes After Liver Transplantation. Issue 7 (July 2017) - Chang, Su-Hsin; Liu, Xiaoyan; Carlsson, Nils P.; Park, Yikyung; Colditz, Graham A.; Garonzik-Wang, Jacqueline M.; Chapman, William C.; Wellen, Jason R.; Doyle, Maria B.; Alhamad, Tarek
Abstract : Background: Several studies have shown that obese patients undergoing liver transplantation (LT) have an increased risk of mortality regardless of Model of End Stage Liver Disease (MELD) scores. The purpose of this study is to identify the range of body mass index (BMI) at LT associated with the lowest risks of posttransplant mortality by MELD category. Methods: A retrospective cohort of patients aged 18 years or older from the Organ Procurement and Transplantation Network database undergoing LT between February 27, 2002, and December 31, 2013, was identified and followed up through March 14, 2014. Patients' MELD score at the time of transplantation was categorized into 10 or lower (MELD1), 11 to 18 (MELD2), 19 to 24 (MELD3), and 25 or higher (MELD4). Multivariable adjusted Cox proportional hazard analyses were conducted. Results: Among 48 226 patients in the analytic cohort (14.8% were in MELD1, 33.7% were in MELD2, 19.6% were in MELD3, and 32.0% were in MELD4), 25% died with mean follow-up of 1371 days. For MELD1, patient BMI ranging from 30 to 33 was associated with a better survival outcome than BMI less than 30 or 33 or greater; for MELD2, BMI ranging from 28 to 37 had a better survival outcome than BMI less than 28 or 37 or greater; for MELD3, the survival outcome improved with an increasing BMI; for MELD4, the survival outcome was not associated with patient BMI. Conclusions: This study provides evidence that obesity in LT patients is not necessarily associated with higher posttransplantation mortality and highlights the importance of the interaction between BMI and MELD category to determine their survival likelihood. Abstract : Supplemental digital content is available in the text.